2006
DOI: 10.1007/bf03167961
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and long term outcome of home vs hospital initiated thrombolysis

Abstract: Pre-hospital thrombolysis by MCCU is feasible and allows significant reduction in the delay time to treatment initiation. There are encouraging improvements in short- and long-term survival with no apparent reduction in safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…One meta‐analysis, 13 three randomised controlled trials 16 ‐ 18 and three cohort studies 27 29 were included. In non‐tertiary hospitals, PHT may be most suitable as a substitute for IHT, and multiple studies have evaluated its role in this setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One meta‐analysis, 13 three randomised controlled trials 16 ‐ 18 and three cohort studies 27 29 were included. In non‐tertiary hospitals, PHT may be most suitable as a substitute for IHT, and multiple studies have evaluated its role in this setting.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, three further studies have shown a mortality benefit and a significant reduction in CS with PHT compared with IHT 27 . ‐ 29 …”
Section: Resultsmentioning
confidence: 99%